Six Communication Keys as the Foundation for Schools to Build Communication with the Community - Jakfar Sodik (Journal of Research in Educational Management, 2023)
This study aimed to find out the application of the six communication keys used by SDN Betek Taman 01 as the basis for building relationships with the community. This research was conducted using a qualitative approach with a case study type. The location of this research was SDN Betek Taman 01. The data collection techniques used in this study were observation, interviews, and documentation. Data sources include the school principal, the vice public relations head, and two student guardians. Data analysis was carried out through three steps, namely; 1) data condensation; 2) data presentation; and 3) drawing conclusions and verification. To get the validity of the data is done by the process of triangulation of sources and techniques. SDN Betek Taman 01 realizes that educational institutions do not stand independently, so the community's existence must be the key to building a good image for the school. Of the six principles of communication (Qaulan Sadida, Qaulan Baligha, Qaulan Ma'rufa, Qaulan Karima, Qaulan Layyinan, and Qaulan Maysura) that have been applied, it explains that the school first establishes a reciprocal or two-way relationship with the school community as in educators and education staff, students, and parents of students. The six principles above represent the four values in communication: respect, cooperation and understanding, and modesty. These communication principles are also the key in upholding the dignity of humanity as a whole, educating humans constantly to respect and maintain respect for themselves and others.